Development and validation of the K‐VSCOR for scoring Koebner's phenomenon in vitiligo/non‐segmental vitiligo. (30th January 2013) - Diallo, Abou; Boniface, Katia; Jouary, Thomas; Seneschal, Julien; Morice‐Picard, Fanny; Prey, Sorilla; Cario‐André, Muriel; Mazereeuw‐Hautier, Juliette; Taieb, Alain; Ezzedine, Khaled
Summary The relation of vitiligo/non‐segmental vitiligo (NSV) to Koebner's phenomenon is variably appreciated. Our objective was to develop and validate a simple clinical score for Koebner's phenomenon (KP) in patients with vitiligo/NSV. The study population was composed of 351 individuals in the development sample and 285 patients in the validation sample. Seven variables were independently associated with the presence of KP: disease duration of more than 3 yr, forehead + scalp areas, eyelids, wrists, genital + belt areas, knees and tibial crests. The score computed by the weighted sum of the rounded coefficients of these seven variables ranged from 0 to 56 (mean 38.39 ± 22.93). The probability of having KP was computed as follows: exp (−2.37 + 0.1*score)/exp [1 + (−2.37 + 0.1*score)]. When applying the score to each patient in the validation and the development sample, the score maintained adequate discrimination and calibration (AUC‐ROC = 0.78), arguing that KP can be adequately predicted using our score. Further studies should evaluate KP assessed by the K‐VSCOR in clinical practice with the aim to determine its association with clinical profile, course and treatment response of vitiligo.